The, A Evaluasi Risiko Lebih Bayar PPh 21 Akibat Implementasi Tarif Efektif Rata-Rata (TER) Di CV. X - adwalaila mayang sherra; nurul fitriani (Jurnal Ilmiah Wahana Akuntansi, 2025)
This study aims to evaluate the risk of overpayment of Income Tax Article 21 (PPh 21) due to the implementation of the Average Effective Rate (TER) at CV. X. The TER scheme was introduced as a simplification of tax administration in accordance with Government Regulation No. 58 of 2023. However, in practice, the use of TER has led to potential tax overpayments, particularly among employees with irregular income. This research employs a qualitative descriptive approach using interview, documentation and observation as data collection techniques. The result of the analysis showed that fluctuating annual income, such as bonuses and religious holiday allowances (THR), caused a mismatch between withheld tax and actual tax liability, leading to an overpayment of IDR 1,141,313. The study recommends mitigation strategies including regular annual PPh 21 simulations, allocating irregular income to the final tax period, and utilizing the tax overpayment compensation mechanism. This research contributes to more efficient tax management practices and encourages adaptability to income variability in companies.